The Effect of Work Motivation and Career Development on Employee Work Productivity at PT Hartono Istana Teknology (Polytron) - Anetta Mutiara Radjiky; Sri Murwanti (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the effect of Work Motivation and Career Development on Employee Productivity at PT Hartono Istana Teknologi (Polytron). The population of this study is all employees, with a sample of eighty two respondents with predetermined criteria. The research used a quantitative approach with primary data obtained from questionnaires distributed via Google forms. The sampling technique used purposive sampling, while data analysis was conducted through validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and coefficient of determination tests. The results of the study indicate that Work Motivation has a positive and significant effect on Work Productivity, as does Career Development. Simultaneously, both variables have a significant effect on Work Productivity.